An investigative study to style reading: The style of Cristobal Balenciaga interpreted by contemporary fashion designers - RANATHUNGA G. M.; WIJESUNDARA K.M.S.V (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: There is a constant recycling of old looks into the current fashion scene. Many working fashion designers today mine haute couture and the works of other high-end designers for inspiration. Fashion designer Cristobal Balenciaga (1895-1972), often called the "king of haute couture," is credited with several groundbreaking looks. Many extraordinary innovations in the world of fashion were gifts from his combination of technical brilliance and aesthetic taste. His contributions are timeless, and they continue to impact fashion designers everywhere. This research aims to analyze contemporary fashion designers Greth Pugh (1981) and Demna Gvasalia (1981) to determine what elements of Balenciaga’s designs have been adopted by them. Methodology: This study takes a qualitative approach. To better understand the work of modern designers, this study examines a wide range of resources, including historical masterpieces, scholarly works, photographs, fashion, museum websites, web articles, books, video documentaries, and informative videos from YouTube channels like the Met and V&A. Through systematic data collection, analysis, and observation were applied to gather the required data. Findings: Cristobal Balenciaga’s ideology has influenced contemporary designers, as evidenced by comparing their work to that of the Masters of the 1950s. All of the chosen designers have clearly absorbed Balenciaga’s masterful inspiration. These two contemporary designers have taken inspiration from the conceptualization of Cristobal Balenciaga’s masterpieces and have updated these ideologies to reflect the current era by fusing new technologies and concepts. Balenciaga’s superiority, however, has stayed the same. Implications/Novel Contribution: This study compares and contrasts Cristobal Balenciaga’s work with modern designers to draw conclusions about how one style can be interpreted in various ways over time. The study opened new avenues of exploratory research in the field for comparative approaches in fashion design industry and research.